2017
DOI: 10.11604/pamj.2017.27.88.8817
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of soil transmitted helminths among school children of Mendera Elementary School, Jimma, Southwest Ethiopia

Abstract: IntroductionSoil transmitted helminths are wide spread in developing countries and in Ethiopia the prevalence of STHs varies in different parts of the country. The aim of this study was to determine the prevalence and intensity of soil transmitted helminths among school children of Mendera Elementary School Jimma town, Southwestern Ethiopia.MethodsA cross-sectional study was conducted between March 29 and April 9, 2010 to determine the prevalence and intensity of soil transmitted helminths among elementary sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
36
5
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 6 publications
13
36
5
3
Order By: Relevance
“…Our result revealed that, more than half of the children harbored at least one species of intestinal helminths, majority being STHs and S. mansoni. This indicates that high burden of the infections exists among the school children, comparable with most of similar previous studies done in Ethiopia [18][19][20]. On one hand, we presumably feel that the one round of annual MDA with mebendazole (single dose, 500 mg) which was given to the school children (6 months before conducting this study), might have influenced the current prevalence obtained.…”
Section: Discussionsupporting
confidence: 84%
“…Our result revealed that, more than half of the children harbored at least one species of intestinal helminths, majority being STHs and S. mansoni. This indicates that high burden of the infections exists among the school children, comparable with most of similar previous studies done in Ethiopia [18][19][20]. On one hand, we presumably feel that the one round of annual MDA with mebendazole (single dose, 500 mg) which was given to the school children (6 months before conducting this study), might have influenced the current prevalence obtained.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, T. trichiura which is estimated 24% among STHs infection prevalence in Ethiopia from SSA prevalence proportion [4,6], is found to be much lower (8.9%) among school children in Dembi district. This prevalence has also been lower than the previous school (23.1%) and community (57%) based study in Jimma/Ethiopia [34] and Peninsular Malaysia [32], respectively suggesting that relatively better toilet facilities, good hand washing habit and better awareness about health in the current study area.…”
Section: Discussioncontrasting
confidence: 70%
“…[5] and 28.9% south Gondar [33], 23.6% in Jimma [34], and 37.2% in Bushulo village [35]. Lower prevalence value of A. lumbricoides also reported in Kenya [21] and Malaysia [32] with a prevalence of 4.9% and 23.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Male students usually play outdoors and participate in outdoor activities compared to females, which may enhance the risks of IPI. However, this finding contradicts with another study conducted in Ethiopia ( 30 ).…”
contrasting
confidence: 86%